Engine room thermal density specials in heating systems shutdow process - M. A. Razakov (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Consider the effect of heating system turning off process on the engine room thermal density in a high-voltage city sewage pumping station. Determine how the heating system shutdown affects to the considered room thermal regimes with unchanged requirements for the indoor air microclimate thermal and moisture parameters. Do a numerical experiment which simulates the stationary thermal regime of engine room and taking into account the main technological process in this room of a high-voltage city sewage pumpingstation. Perform adaptation of thermal regime developed model to simulate the heating system turning off process. Describe the distribution of heat losses in the engine room while maintaining a constant air temperature. METHODS. When solving the task, author has used the method of calculating the engine room design stationary mode.RESULTS. Researcher describes the relevance of the topic, considers the specials of the change in the engine room thermal density when the heating system is turned of and other factors. Author has presented the results of the thermal excesses calculation for different numbers of operating pumps and changes in wastewater temperature.CONCLUSION. The turning off process of the heating system reduces the thermal density of the engine room by an average of 0.3 - 0.4 W/m3. This method of energy saving helps to reduce the consumption of thermal energy and could be used in this part of sewage pumping station. The economical effect of proposed energy saving measurement will be in economical index reducing. It will be 890 000 rubles saving per year for this type of sewage pumping station in designed mode.